Morocco : Request for an Arrangement Under the Precautionary and Liquidity Line: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2012)
Morocco's track record of sound economic policies helped it withstand the recent economic crisis and regional social events. High oil prices have contributed to a build-up of fiscal and external pressures, but the government has taken action to address these vulnerabilities and are committed to continuing implementation of sound policies. Morocco has sound economic fundamentals and institutional policy frameworks, and performs strongly on three of the five Precautionary and Liquidity Line (PLL) qualification areas. A precautionary arrangement would support the policies by providing a financing buffer against exogenous shocks.